Focused Electron Beam Induced Processing Renders at Room Temperature a Bose-Einstein Condensate in Koops-GranMat - Koops, Hans W.P. (Journal of Coating Science and Technology, 2016)
Focused Electron Beam Induced Processing allows to generate nanocrystalline materials with metallic conductivity and also nanogranular materials with metal crystals embedded in a fullerene matrix, which shows at room temperature 1000 times better conductivity than superconductors at 40 K due to a Bose Einstein Condensate. Resistors and field emitters carry > 50 MA/cm² current density and deliver up to 1 mA current by field emission, when having an enlarged foot point contact to normal metal like Gold. An explanation for the different characteristics is given. The reason for the generation of the Bose Einstein Condensate is explained, and applications are described.